2007
DOI: 10.1111/j.1476-4431.2006.00203.x
|View full text |Cite
|
Sign up to set email alerts
|

C‐reactive protein, tumor necrosis factor α, and interleukin‐6 in dogs with pyometra and SIRS

Abstract: Objective: To determine the frequency of the systemic inflammatory response syndrome (SIRS) in canine pyometra and to evaluate the relationship between C‐reactive protein (CRP), tumor necrosis factor α (TNFα), interleukin‐6 (IL‐6), and SIRS.Design: Prospective clinical study.Setting: Veterinary teaching hospital.Animals: Fifty‐three clinical cases of canine pyometra and 19 healthy control bitches.Interventions: Upon admission to the veterinary hospital, history and physical examination findings, including… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

21
101
3
8

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 95 publications
(133 citation statements)
references
References 35 publications
21
101
3
8
Order By: Relevance
“…Oxidative stress was not obviously occurred in PG in this study and also this might reflected on the mortality rate. Respiratory and heart rates and body temperatures were similar with the previous studies [5,15] . Breed distribution in PG was similar with the breeds with high risk, but three German shepherd bitches in PG that was determined to have a low risk of developing pyometra was in contrast by Egenvall et al [4] .…”
Section: Discussionsupporting
confidence: 77%
See 4 more Smart Citations
“…Oxidative stress was not obviously occurred in PG in this study and also this might reflected on the mortality rate. Respiratory and heart rates and body temperatures were similar with the previous studies [5,15] . Breed distribution in PG was similar with the breeds with high risk, but three German shepherd bitches in PG that was determined to have a low risk of developing pyometra was in contrast by Egenvall et al [4] .…”
Section: Discussionsupporting
confidence: 77%
“…Microcytic anaemia in PG may be occurred because of the blood loss into the uterus, iron deficiency, and toxic effects of the pyometra on the bone marrow or lipid peroxidation damage on erythrocytes membranes. In contrast with the other studies [5,18] none of the biochemical variables were found significantly different between the groups, before and 15 days after OVH. PLT was significantly lower in PG before the OVH, but increased after 15 days.…”
Section: Discussioncontrasting
confidence: 53%
See 3 more Smart Citations